1998
DOI: 10.1128/jb.180.4.901-908.1998
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Cloned DNA Map of the Genome of Vibrio cholerae 569B and Localization of Genetic Markers

Abstract: By using a low-resolution macrorestriction map as the foundation (R. Majumder et al., J. Bacteriol. 176:1105–1112, 1996), an ordered cloned DNA map of the 3.2-Mb chromosome of the hypertoxinogenic strain 569B of Vibrio cholerae has been constructed. A cosmid library the size of about 4,000 clones containing more than 120 Mb ofV. cholerae genomic DNA (40-genome equivalent) was generated. By combining landmark analysis and chromosome walking, the cosmid clones were assembled into 13 contigs covering about 90% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…In our study, a 3AE5 kb band was uniformly detected in all strains (100%) which might be attributed to the incomplete copy of IS1004 in the rfb locus. It has been indicated that the copy numbers of IS1004 element in V. cholerae O1 El Tor strains are different from classical strain 569B, containing 5-6 and 10 copies, respectively (Bik et al 1996;Chatterjee et al 1998). IS1004 profiles of all V. cholerae O1 strains in our study (El Tor biotype) were identical and indistinguishable from V. cholerae O1 ATCC14035 (classical biotype).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In our study, a 3AE5 kb band was uniformly detected in all strains (100%) which might be attributed to the incomplete copy of IS1004 in the rfb locus. It has been indicated that the copy numbers of IS1004 element in V. cholerae O1 El Tor strains are different from classical strain 569B, containing 5-6 and 10 copies, respectively (Bik et al 1996;Chatterjee et al 1998). IS1004 profiles of all V. cholerae O1 strains in our study (El Tor biotype) were identical and indistinguishable from V. cholerae O1 ATCC14035 (classical biotype).…”
Section: Discussionmentioning
confidence: 43%
“…IS1004 is an active mobile genetic element and is able to transpose in V. cholerae O1 classical and El Tor strains which has been exclusively described as an epidemiological marker (Chatterjee et al 1998;Nesper et al 2000). It comprises of about 628 bp, with no terminal inverted repeats (Bik et al 1996) which has been applied successfully for strain differentiation of V. cholerae strains.…”
Section: Introductionmentioning
confidence: 99%
“…al. [11] in our laboratory. The control and experimental hybridizations were performed at least thrice by reusing the same blot.…”
Section: Resultsmentioning
confidence: 99%
“…Each cosmid clone contained an insert of V. cholerae genomic DNA between 20 and 40 kb. The restriction map of each clone was veri-¢ed with the original data [11], to check for deletions. The clones containing rrn operons were excluded as they gave saturated values and caused errors during calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation